Clash of the clouds. (Economist, 2009)
The article discusses a controversy concerning cloud computing. A manifesto supported by International Business Machines and others calls for open standards and portability of data and applications among different providers of cloud services. However firms such as Amazon.com and Google, which have established significant cloud operations, have their objections.